PENGGUNAAN MEDIA PEMBELAJARAN PPT CANVA UNTUK MENINGKATKAN CAPAIAN NUMERASI PELAJARAN MATEMATIKA KELAS II SD NEGERI BUGANGAN 03 KOTA SEMARANG - Desi Ratna Haryati; Ayu Nyoman Murniati, Ngurah; Mas'udah; Mudzanatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Numeracy ability is a very important basic ability for students to have which becomes a reference in understanding science and other basic knowledge in everyday life. To create good numeracy skills in students, teachers must be able to create a pleasant learning atmosphere. This can be realized with the Canva ppt learning media. Learning media is a learning tool that is used by teachers as intermediaries to convey instructional materials in the learning process so as to facilitate the achievement of teaching objectives. This research aims to analyze students' numeracy abilities regarding mathematics subject matter, learning motivation and also the use of learning media by teachers. This research uses descriptive qualitative method. This research was conducted at SD Negeri Bugangan 03 Semarang City, involving a teacher and 28 fifth grade students. Researchers collected data through structured interviews with fifth grade teachers, observing the learning process twice, and documentation in the form of photos, audio, and video. The data analysis technique used by researchers is the Miles and Huberman model which includes data reduction, data display, and drawing conclusions. The researcher's data validity technique used the credibility test and confirmability test. In testing the credibility of the data, researchers used ways to increase persistence in research, triangulation, and member checks. The results of the analysis show that using the Canva ppt learning media has a positive impact on increasing students' numeracy skills and learning motivation.